Genotypes and associated traits in Salmonella enterica Newport strains linked to fresh produce-associated outbreaks in the United States - Carter, Michelle Qiu; Carychao, Diana; Gorski, Lisa; Lindsey, Rebecca L.; Bono, James L. (Frontiers in Microbiology, 2026)
Salmonella enterica is a leading cause of bacterial infection in humans and animals. Newport is among the most prevalent serotypes linked to fresh produce-associated salmonellosis outbreaks in the United States and among the top serotypes that cause foodborne outbreaks overall. In this study, comparative pathogenomic analyses and phenotypic assays were performed to uncover genetic and phenotypic traits contributing to pathogenicity and epidemiological prevalence of Newport. The 10 clinical strains were placed in four sequence types (ST5, ST31, ST45, and ST118) using classical MLST method and 10 SNP clusters using NCBI Pathogen Detection pipeline. Of the 10 SNP clusters, several persistent genotypes were identified, including PDS000127718 and PDS000029636, and each contained more than 4,000 matched strains and had been detected over a long period of time (> 20 years). In contrast, some SNP clusters appeared to represent transient genotypes, such as PDS000002512 that contained less than 10 matched strains and had been detected within a short period of time (< 5 years). The core virulence determinants in Newport included SPI-1 and SPI-2 encoded T3SS, SPI-4 and SPI-9 encoded T1SS, SPI-6 encoded T6SS, and many fimbriae and nonfimbrial adhesins. Among the seven SPIs detected, SPI-6 exhibited the greatest sequence divergence, including a large deletion that abolished both T6SS and Saf fimbriae simultaneously. Of the 11 fimbriae examined, Peg and Ste fimbriae genes were detected only in the lineage II strains while Stc fimbriae genes were detected only in the lineage III strains. Vast strain variation was revealed in expression of curli fimbriae, biofilm formation, and adherence to cantaloupe rind. Expression of curli fimbriae appeared to be strain-specific and was not associated with ST or lineage. Under the condition tested, curli enhanced biofilm formation significantly but tempered adherence of Newport to cantaloupe rind, implying a role of other adhesins in the initial interaction between Newport cells and the surface of cantaloupe rind. More accessory genes were identified in strains with a persistent genotype than in strains with a transient genotype, suggesting a role of accessory genes in dissemination of S. enterica Newport.